Understanding the Limitations of Research - Salas-Blas, Edwin (2019)
This work is an argumentative essay, or, in the terms of Montero and León (2005), it is a theoretical study. Its objective is to critically propose an evaluation of the state in which psychological research is in Peru, and from this analysis, raise the potential reasons for the problematic situation and reflect on these aspects, in order to finally propose ideas for solving the problems detected. For its purpose and the kind of discourse that is managed in it, this could be useful for students or work teams that wish to conduct deeper, empirical (quantitative or qualitative) or non-empirical research, about the topic of  psychological research in Peru.